Rancang Bangun Heat Exchanger Tube Non Fin Satu Pass, Shell Tiga Pass Untuk Mesin Pengering Empon-Empon - Setiawan, Dona; , Sartono Putro, Ir.,M.T (2017)
Heat Exchanger is device that facilitate the exchange of heat between two fluids that are at different temperatures while keeping them from mixing with each other. This research is aimed at fidding an influence of mass flow rate variety of Heat Exchanger tube non fin one pass and shell three pass for turmeric drainage. The mass flow rate variety 0,027, 0,030, and 0,32 kg/s The steps of Heat Exchanger is, first, cold fluid such as air from the blower to flow into the heat exchanger, in the heat exhanger cold fluid will receive heat from hot fluid flowing in a shell that is pre-heated by the stove, and after that cold fluid is out of heat exchanger and into the engine medicinal dryer. The optimum heat found at variety of cold fluid mass flow rate 0.032 kg/s. The result of this research show that, if the cold fluid mass flow rate of air are bigger, it is means that temperature different dan heat of cold fluid mass flow rate is bigger.